Anticancer studies of drug encapsulated polyethylene terephthalate-Co-polylactic acid nanocapsules - K Sathish Kumar; P Senthil Kumar; S Vijayalakshmi (Wolters Kluwer Medknow Publications, 2011)
Objectives: The purpose of this study was to investigate the anticancer activity of anticancer drugs (5-fluorouracil and 6-thioguanine) in polymeric nanocapsules in the presence and in the absence of gold and iron oxide nanoparticles toward Hep2 cancer cells. Materials and Methods: MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay was used for quantitative measurements for the anticancer cell activity. Encapsulated drug in polyethylene terephthalate-polylactic acid copolymer (PET-co-PLA) nanocapsules in the presence and absence of gold and iron oxide nanoparticles were prepared via the W/O/W emulsification solvent-evaporation method. Morphology of the nanoparticles was characterized by transmission electron microscopy and scanning electron microscopy. Conclusion: The average size of the polymeric nanocapsules, gold nanoparticles, and iron oxide nanoparticles were found to be in range of 230-260, 18 -20 nm, 5-10 nm, respectively. The findings in this study inferred that incorporated drug in polymeric nanocapsules with gold nanoparticles and iron oxide nanoparticles show better anticancer activity when compared with encapsulated drug in polymeric nanocapsules.